2019
DOI: 10.11152/mu-1774
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced carotid ultrasonography and MRI plaque imaging to identify patients developing in-stent intimal hyperplasia after carotid artery stenting

Abstract: Aim: In-stent intimal hyperplasia (ISH) observed after carotid artery stenting (CAS) may lead to in-stent restenosis. We aimed to investigate whether contrast-enhanced carotid ultrasonography (CEUS) and magnetic resonance imaging (MRI) plaque imaging prior to CAS are predictive for ISH at 6 months after CAS.Material and method: A total of 14 patients (13 men, 1 woman; mean age, 74.2 years) were prospectively enrolled. CEUS and MRI plaque imaging were performed before CAS. ISH was diagnosed by carotid angiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…We conducted a systematic literature review without meta-analysis per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [8]. Nineteen studies were identified that discussed perioperative risk in the context of relevant anatomy [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1) in addition to fourteen studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 2) and fifteen case reports/series [42][43][44][45][46][47][48][49][50][51][52][53][54]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We conducted a systematic literature review without meta-analysis per Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines [8]. Nineteen studies were identified that discussed perioperative risk in the context of relevant anatomy [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1) in addition to fourteen studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41] (Table 2) and fifteen case reports/series [42][43][44][45][46][47][48][49][50][51][52][53][54]…”
Section: Resultsmentioning
confidence: 99%
“…Recent trial data comparing the two was found to be equivocal for short and long-term primary endpoints, and continued analysis in pooled studies reported increased risk of AIS in the first month following CAS [70][71][72]. As such, early guidelines recommended CAS to be reserved as an alternative to CEA in anatomically favorable scenarios [1,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Anatomic factors often dictate treatment outside of CAS, such as during emergent EVT and PTA in the context of AIS secondary to LVO or intima dissection [73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 In addition, another study with a small sample size showed that plaques detected by contrast-enhanced ultrasound (CEUS) were significantly correlated with in-stent intimal hyperplasia. 10 CEUS can observe IPN through the degree of microbubble enhancement and can be used as a screening method to detect plaque vulnerability. However, to our knowledge, the predictive value of carotid plaque characteristics assessed using CEUS for ischaemic events in patients after CAS has not been discussed.…”
Section: Introductionmentioning
confidence: 99%